Teachers’ Perspectives on the Impact of English Immersion on Spanish Language Development in Primary Education - Giraldo Gómez, Jorge Andrés; Pabón García, Marinessa; Escobar Puerta, ¨Paola Andrea; Castrillón Ángel, Edison Ferney (Colombian Applied Linguistics Journal, 2025)
This study analyzed the effects of constant exposure to English as a foreign language on developing Spanish as the first language among elementary school students. This research study was oriented from a historical hermeneutical paradigm, using a qualitative approach and a narrative inquiry. The study involved English language, Spanish language, and pedagogical support from teachers who examined students’ bilingual learning experiences. The researchers applied four data collection techniques: an observation guide, an open-ended survey, a semi-structured interview, and a questionnaire, all of which sought to highlight the importance of a balanced approach to language education that values and supports the development of first and foreign languages. This integrated perspective was vital for ensuring students can effectively navigate the complex landscape of learning languages while preserving their personal, linguistic, and cultural identities. The study highlights the importance of balancing learners' native language with English proficiency, emphasizing cultural preservation and linguistic identity for thriving in a globalized world.